Bortezomib with standard chemotherapy for children with acute myeloid leukemia does not improve treatment outcomes: a report from the Children’s Oncology Group - Aplenc, Richard; Meshinchi, Soheil; Sung, Lillian; Alonzo, Todd; Choi, John; Fisher, Brian; Gerbing, Robert; Hirsch, Betsy; Horton, Terzah; Kahwash, Samir; Levine, John; Loken, Michael; et al. (Haematologica (Roma), 2020)
New therapeutic strategies are needed for pediatric acute myeloid leukemia (AML) to reduce disease recurrence and treatment-related morbidity. The Children's Oncology Group Phase III AAML1031 trial tested whether the addition of bortezomib to standard chemotherapy improves survival in pediatric patients with newly diagnosed AML. AAML1031 randomized patients younger than 30 years of age with AML to standard treatment with or without bortezomib. All patients received the identical chemotherapy backbone with either four intensive chemotherapy courses or three courses followed by allogeneic hematopoietic stem cell transplantation for high-risk patients. For those randomized to the intervention arm, bortezomib 1.3 mg/m was given on days 1, 4 and 8 of each chemotherapy course. For those randomized to the control arm, bortezomib was not administered. In total, 1,097 patients were randomized to standard chemotherapy (n=542) or standard chemotherapy with bortezomib (n=555). There was no difference in remission induction rate between the bortezomib and control treatment arms (89% 91%, =0.531). Bortezomib failed to improve 3-year event-free survival (44.8±4.5% 47.0±4.5%, =0.236) or overall survival (63.6±4.5 67.2±4.3, =0.356) compared with the control arm. However, bortezomib was associated with significantly more peripheral neuropathy ( =0.006) and intensive care unit admissions ( =0.025) during the first course. The addition of bortezomib to standard chemotherapy increased toxicity but did not improve survival. These data do not support the addition of bortezomib to standard chemotherapy in children with AML. (Trial registered at ).